The peer review process: a primer for JNIS readers. (17th April 2015) - Hirsch, Joshua A; Manchikanti, Laxmaiah; Albuquerque, Felipe C; Leslie-Mazwi, Thabele M; Lev, Michael H; Linfante, Italo; Mocco, J; Rai, Ansaar T; Schaefer, Pamela W; Tarr, Robert W
Abstract : Peer review of scientific articles submitted for publication has been such an integral component of innovation in science and medicine that participants (be they readers, reviewers, or editors) seldom consider its complexity. Not surprisingly, much has been written about scientific peer review. The aim of this report is to share some of the elements of that discourse with readers of the Journal of NeuroInterventional Surgery ( JNIS ).